Effect of electron beam irradiation on the morphology of alumina ceramic - Purwanto, Hadi; Othman, Nur Ezzah Faezah; Zaini, KH; Abdullah, Yusuf (2015)
There has been an increased interest in improving the properties of alumina ceramic to be used in nuclear applications. This paper focuses on the effect of electron beam irradiation on the morphology of alumina ceramic. Alumina ceramic pellet was prepared by compacting of fine alumina powder then subjected for sintering process at 1500ºC for 2 hours using electrical heating furnace. Then, the pellets were irradiated with electron beam of total dose 200 kGy with vary of electron beam speed of 100kGy/pass and 25kGy/pass. Scanning Electron Microscope and Atomic Force Microscope were used to observe the morphology of the sample. The results show that the irradiation changes the grain of the alumina ceramic due to bonding of particles caused by energy from electron beam especially at high speed. Furthermore, the surface roughness decreases after irradiation and become lower at low speed. Finer grain is obtained on the surface after irradiated at lower speed. The high energy of electron beam destroyed the particles during long contact period to the surface when low speed of electron beam is applied.